2018
DOI: 10.1177/0883073817750501
|View full text |Cite
|
Sign up to set email alerts
|

Stroke After Minor Head Trauma in Infants and Young Children With Basal Ganglia Calcification: A Lenticulostriate Vasculopathy?

Abstract: The authors retrospectively reviewed charts of the children with basal ganglia stroke who either had preceding minor head injury or showed basal ganglia calcification on computed tomography (CT) scan. Twenty children, 14 boys and 6 girls were identified. Eighteen were aged between 7 months to 17 months. Presentation was with hemiparesis in 17 and seizures in 3. Preceding minor head trauma was noted in 18. Family history was positive in 1 case. Bilateral basal ganglia calcification on CT scan was noted in 18. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 31 publications
1
52
0
1
Order By: Relevance
“…Remarkably, nine of them were found to have anemia (hemoglobin < 11 g/dL), with microcytosis in six and low serum iron or low ferritin in 11 individuals. On the other hand, IDA was not mentioned as a risk factor or finding in all remaining published cases of mineralizing angiopathy 1,5,[8][9][10][11][12][13][14][15]20 despite the high prevalence of IDA in exactly this age group.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Remarkably, nine of them were found to have anemia (hemoglobin < 11 g/dL), with microcytosis in six and low serum iron or low ferritin in 11 individuals. On the other hand, IDA was not mentioned as a risk factor or finding in all remaining published cases of mineralizing angiopathy 1,5,[8][9][10][11][12][13][14][15]20 despite the high prevalence of IDA in exactly this age group.…”
Section: Discussionmentioning
confidence: 93%
“…Basal ganglia calcification was identified in 44.8% of individuals with mild head trauma, though in none of the controls. Goraya et al 15 reported recently on a retrospective study of 20 children with basal ganglia stroke who either had a preceding minor head injury or showed basal ganglia calcification on CT. Eighteen were aged between 7 months and 17 months. Bilateral basal ganglia calcification was noted in 18/20 children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations